Entrepreneurial potential and career choice regret: A focus on switching intention among employees and entrepreneurs in the DRC - Ephrem, Akilimali Ndatabaye (University of the Witwatersrand, Johannesburg, 2023)
This thesis is made of four pieces. In the first piece, it is shown that as good as extant measurement scales of entrepreneurial potential might appear in the literature, they suffer from the lack of theory integration and clarity and are fragmented among ‘siloed’ scholars repeating each other without real progress. Through several studies, the thesis develops and validates a new entrepreneurial potential scale, therefore setting an important pre-condition for advancing entrepreneurship theory and practice. The remaining thesis problematizes that, despite the merit of extant studies on career decision regrets, they do not address important questions about the prevalence, the antecedents and consequences of regret arising from choosing entrepreneurship instead of paid employment and vice versa. The thesis examines the mediation role of career choice regret in the relationship between entrepreneurial potential and career switching intention, the moderated effect of entrepreneurial potential on career choice regret, and the moderated effect of the latter on career switching intention. The relationships between the constructs were examined by applying the PLS-SEM on data collected on 721 employees and 724 entrepreneurs from the DRC. In the second piece, it was found out that career choice regret partially mediates the effect of entrepreneurial potential on career switching intention. Thus, a contribution is made to the regret regulation theory by arguing and justifying that, what is or must be regulated is not regret only but also and most importantly the choice and the outcome. In the third piece, evidence is provided that the effect of entrepreneurial potential on career choice regret is moderated by duration in the career, social comparison, former career status, decision justifiability, and perceived environment’s supportiveness. Thus, the thesis reconsiders the regret regulation theory, in particular the propositions that relate to regret cyclicity, decision justifiability and external attributions of regret. In the fourth piece, the thesis examines when individuals consider reversing their career choices to manage regrets. By doing so, the thesis does not only test but also clarifies and extends the regret regulation theory in relation to the post- decision regret management strategies. The findings indicate that individuals consider reversing career choices to manage regrets when: (1) the foregone career is accessible and resistance to change does not prevail; (2) it is not yet too late to do so; (3) they never tried the forgone option or, mistakenly or strategically gave up on it; (4) the decision can benefit from sincere social support and approval of referent individuals; and (5) can advance valued active goals. Overall, the thesis offers novel human resource management and entrepreneurship policy implications
A thesis submitted to the Graduate School of Business Administration, Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy in Management, Johannesburg 2023
Keywords: Entrepreneurial potential; Career choice regret; Scale development and validation; Regret regulation theory; Career switching intention; Paid employment; entrepreneurship; UCTD; SDG-8: Decent work and economic growth